Van Riemsdijk, Micheline i Wang, Qingfang (2017). Rethinking international skilled migration - Ortiz Guitart, Anna (Documents d’Anàlisi Geogràfica, 2018)
Van Riemsdijk, Micheline i Wang, Qingfang (2017) Rethinking international skilled migration Oxon: Routledge, 311 p. ISBN 9781317420767